Clive Cussler's Dark vector : a novel from the NUMA files - Brown, Graham, 1969-; Cussler, Clive (New York : G.P. Putnam's Sons, 2022)
"A freighter carrying top-secret computers of unparalleled capability disappears in the Western Pacific. While searching for a lost treasure that once belonged to the famous Chinese pirate queen, Ching Shih, Kurt Austin and Joe Zavala are redirected to look for the missing vessel. Discovering that the sinking of the ship is just part of an intricate web of deception, they find themselves in the middle of a cyber-war between rival groups of hackers, both of whom want to control the flow of data around the world. With no allies except a group of pirates who operate under their own crude laws, Kurt and Joe must rescue a colleague held hostage--while keeping the computers out of Russian or Chinese hands and the world's digital information safe from the hackers"--
Keywords: Austin, Kurt -- (Fictitious character) -- Fiction; National Underwater and Marine Agency -- Fiction; Marine scientists -- Fiction; Pirates -- Fiction; Cyberterrorism -- Prevention -- Fiction; Thrillers (Fiction); Action and adventure fiction; Novels